UJI EFEKTIVITAS ANTIBAKTERI SABUN CUCI TANGAN YANG MENGANDUNG PERASAN JERUK KALIMANSI (Citrofotunella microcarpa) - Dian Handayani; Delia Komalasari; Buistu Arbaa Nuyuh Putri; Dinda Zulkarnain; Kurnia Hafidzah; Rizki Hadi Wibowo; Dwi Dominica (Jurnal Ilmiah Manuntung: Sains Farmasi Dan Kesehatan, 2022)
Kalamansi orange with the Latin name Citrofortunella microcarpa is an agricultural commodity that has been widely developed in Bengkulu Province. This study aims to determine the anti-bacterial activity of hand washing soap containing kalimansi orange juice against pathogenic bacteria, one of which is the bacteria S. aureus and E. Coli. The method used in this research is disc paper diffusion. The results of the antibacterial activity test were marked by the formation of a clear area around the disc paper on the media, the largest diameter of inhibition for S. aureus bacteria was given by F2, namely 30.595 mm and the largest diameter of inhibition for E. coli bacteria, which was given by F3, namely 28, 98mm so that it gets a very strong category. When compared to the comparator handsoap in the market HSFFLS @ the inhibitory power of hand washing soap from kalimansi orange juice was also greater both against S.aureus and E. Coli bacteria. The results of the inhibitory activity test between gram-positive and gram-negative bacteria showed that hand washing soap containing kalimansi orange juice had a greater potential for S. aureus gram-positive bacteria compared to Gram-negative bacteria E. Coli.